FACTORS INFLUENCING PURCHASING DECISIONS ON NIKE SHOES (CASE STUDY OF FEB STUDENTS OF BANDAR LAMPUNG UNIVERSITY) - Refael Gustiawan; Herry Goenawan Soedarsa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The shoe market is currently experiencing increased competition. Each brand creates high-quality sneakers. The shoe brand "NIKE" is very popular. The purpose of this study showed the impact of motivational and perceptual variables on Nike shoe purchases. The analysis in this study is quantitative and descriptive. 100 students of the Faculty of Economics and Business, Bandar Lampung University were selected as research samples. Data collection techniques using questionnaires use multiple linear regression to test the data collected. The results of the study concluded that the decision to buy Nike shoes was significantly influenced by motivational variables. In addition, Nike shoe purchase decisions are significantly influenced by perceptual variables. And overall, it can be concluded that the decision to buy Nike shoes is influenced by both variables, namely motivation and perception.